1999
DOI: 10.2331/fishsci.65.362
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of the Effective Population Size during Maintenance of the Guppy Strain

Abstract: The change of gene frequencies at the AAT-1 * and PGM-1 * loci was examined in the two guppy strains, S and S3, which had been maintained as a closed colony for a period of 16 years. These strains had been separated from an original strain in 1981. In the S strain, the *a allele frequency at AA T-1 * locus changed from 0.282 in 1981 to 0.602 in 1997, and the *a allele at the PGM-1 * locus changed from 0.772 to 0.430. On the other hand, in the S3 strain, the *a allele frequency at the AA T-1 * locus changed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…In the present study, allozyme and microsatellite analysis of three naturalized populations and nine domestic strains revealed that genetic variation measured by mean heterozygosity was significantly lower in the domestic strains than in the naturalized populations. As reported in other fish species (Allendorf & Phelps, 1980;Ryman & Ståhl, 1980;Taniguchi et al, 1983;Agnèse et al, 1995), the domestic guppy strains may lose their genetic variation due to bottlenecks at their foundation and through subsequent low effective population sizes (Barinova et al, 1998;Fujio et al, 1999). This is also supported by the previous allozyme data that demonstrates significant decreases in the mean heterozygosity in the domestic guppy strains during 10 years of maintenance, or c. 20-30 generations (Barinova et al, 1997b).…”
Section: Discussionsupporting
confidence: 72%
“…In the present study, allozyme and microsatellite analysis of three naturalized populations and nine domestic strains revealed that genetic variation measured by mean heterozygosity was significantly lower in the domestic strains than in the naturalized populations. As reported in other fish species (Allendorf & Phelps, 1980;Ryman & Ståhl, 1980;Taniguchi et al, 1983;Agnèse et al, 1995), the domestic guppy strains may lose their genetic variation due to bottlenecks at their foundation and through subsequent low effective population sizes (Barinova et al, 1998;Fujio et al, 1999). This is also supported by the previous allozyme data that demonstrates significant decreases in the mean heterozygosity in the domestic guppy strains during 10 years of maintenance, or c. 20-30 generations (Barinova et al, 1997b).…”
Section: Discussionsupporting
confidence: 72%
“…It would occur initially because of a founder effect, the situation in which small numbers of brooders were taken from the natural population for domestication (Allendorf andPhelps 1980, Norris et al 1999). The populations keep facing allele loss during domestication process due to inbreeding and or genetic drift (Fujio et al 1999). The effect of allele loss have been clearly demonstrated in hatchery populations of fi sh and shellfi sh; for example, Atlantic salmon, Salmo salar (Koljenon et al 2002);…”
Section: Resultsmentioning
confidence: 99%
“…Hence F cbased estimators of N e remain frequently used in pracfrequencies were simulated and F c was computed. All simulations were carried out using Mathematica (Woltice (Fujiio et al 1999;Turner et al 1999;Goldringer et al 2001;Shikano et al 2001). Properties of F c -based fram 1996).…”
mentioning
confidence: 99%